DAMPAK LAMA PENGISIAN BATERAI PADA MOBIL LISTRIK TERHADAP MINAT CALON PEMBELI - Putra Ridwan, Brata Pratama (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2023)
Electric cars are transportation with new types of fuel that are being hotly discussed by the public, with the rising price of fossil fuels, making people choose to switch to electric cars to be more efficient and environmentally friendly. Electric cars themselves have many advantages for the environment in addition to not emitting air pollution, electric cars also do not emit noise pollution, which electric cars are very impermeable and do not emit sound. However, chargers in electric cars are one of the main things so that electric cars can be used, chargers are used to charge electric cars. To charge an electric car battery, it takes a long time until the battery is fully charged. Therefore this study will conduct an analysis by reviewing public knowledge of electric cars and how people perceive the long charging time of electric cars. As well as explaining the influence of age, gender, occupation, domicile, monthly spending on cars, intensity of car use, and the government on the impact of long battery charging durations on electric cars on the interest of prospective buyers. The author uses a survey method in the form of an online questionnaire as a means of collecting research data. Testing this research using the One Sample T-Test method in testing the research instrument and followed by the Independent Sample T-Test to test the relationship between two populations that are not related to each other. Based on the results of the analysis, it can be seen that the majority of people still want to buy an electric car even though the duration of charging the battery or power is long.